2017
DOI: 10.1097/bsd.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Postoperative Morbidity and Readmission for Revision Posterior Lumbar Fusion

Abstract: In general, longer, more extensive procedures on sicker patients were associated with increased risk of postoperative complications and readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…Compared to instrumented posterior fusion, instrumented posterior fusion with interbody took an average of 19 minutes of additional time (P , .001). Although operative time has been associated with an increased risk of adverse events in other studies, 34,35 the differences were not associated with different perioperative morbidity in the current study. Thus, the clinical significance of these relatively small differences is thought not to be great in this setting.…”
Section: Discussioncontrasting
confidence: 52%
“…Compared to instrumented posterior fusion, instrumented posterior fusion with interbody took an average of 19 minutes of additional time (P , .001). Although operative time has been associated with an increased risk of adverse events in other studies, 34,35 the differences were not associated with different perioperative morbidity in the current study. Thus, the clinical significance of these relatively small differences is thought not to be great in this setting.…”
Section: Discussioncontrasting
confidence: 52%
“… 24 The impact of obesity was also overestimated by 1.23 relative risk and may be due to recent studies focusing on the effects of this modifiable risk factor. 18 , 25 Finally, the underestimated impact of preoperative anemia, although not statistically significant, may be explained by a stringent American College of Surgeons NSQIP definition for this status. 11 …”
Section: Discussionmentioning
confidence: 96%
“…An analysis of ACS-NSQIP (American College of Surgeons National Surgical Quality Improvement Program) data from 2005 to 2013 found a 30-day readmission rate of 5.8% following lumbar fusion revision surgery. 20 Another previous review of ACS-NSQIP data found that PLIF/TLIF (posterior lumbar interbody fusion/transforaminal lumbar interbody fusion) and ALIF/LLIF (anterior lumbar interbody fusion/lateral lumbar interbody fusion) revision lumbar surgery were associated with a 53% increased odds of morbidity, including bleeding events requiring transfusion. The study, however, found no significant difference between readmission rates in revision versus primary lumbar procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings correlate with previous studies examining risk factors for readmission following lumbar surgery. 20,25,26 This makes sense clinically, given diabetes' association with impaired wound healing, neuropathy, and increased risk of infection. 27 Since there are an increasing number of Americans living with diabetes, 28 it is important for surgeons to identify and medically optimize glycemic levels in patients undergoing elective revision lumbar surgery.…”
Section: Baaj Et Al Conducted An Analysis Of 86 869 Patients Who Recementioning
confidence: 99%